Neuroprotective effects of phloretin and phloridzin on paclitaxel-induced neuronal damage in primary neuron cells - Muhammed Yayla; Harun Ün; Damla Binnetoğlu (Cukurova Medical Journal, 2021)
Purpose: Paclitaxel, is one of the most commonly used chemotherapeutic, causes neuron damage with some serious side effects such as neutropenia and peripheral neuropathy. In current study, we used phloretin and phloridzin to investigate their neuroprotective effects on paclitaxel-induced neuronal damage. Materials and Methods: The neuroprotective effects of phloretin and phloridzin has been analyzed on cell culture of primary neuron cells and evaluated by testing cell viability, total oxidant and total antioxidant capacities and expression of caspase-3, caspase-9 and TNF-α. Paclitaxel administration caused cell death and significant increase of total oxidant levels and activation of apoptotic genes such as caspase-3, caspase-9 and TNF-α. Results: Phloretin and phloridzin treatments at micromolar concentrations reduced paclitaxel-induced cell death by increasing total antioxidant levels. Also these two flavonoids protect neuron cells from apoptosis by decreasing caspase-3, caspase-9 and TNF-α gene expression. For this reason, these molecules may recover the oxidative damage, and restore normal cellular conditions. Conclusion: This study shows the promising neuroprotective ability of the phloretin and phloridzin able to protect neuron cells from injury induced by paclitaxel, actively increasing antioxidant capacity, normalizing oxidant levels and consequently avoiding cell death.